Deatherage, Dorothy (audio interview #1 of 1) - Deatherage, Dorothy; Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This single interview was conducted Deatherage's office in the CSULB Physicial Education Department. The audio quality is good, although the interview was interrupted by a phone call. 2/25/1981